High-resolution study of the tetradecad stretching vibrational bands of MSiD4 (M=28,29,30); Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 236 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Raspopova N. I. Natalya Ivanovna; Kuznetsov A. V. Alexey Valerevich; Sydow C. Christian; Bauerecker S. Sigurd (2019, 2019)
Title screen